China’s national continuing medical education program for general practitioners: a cross-sectional survey (2016–2023) - Conglei You; Lingling Wang; Jian Zhang; Mi Yao (BMC Medical Education)
Abstract Background Pursuing excellence in healthcare delivery systems is an ongoing process. In this process, continuing medical education (CME) is essential for medical professionals to maintain high standards of patient care. In China, where the healthcare sector is undergoing considerable reforms and faces challenges owing to socioeconomic development and demographic shifts, an effective CME system is vital for general practitioners (GPs). Methods A cross-sectional survey of CME programs was conducted between 2016 and 2023. The external characteristics of the programs were systematically gathered and statistically analyzed. The programs were subsequently subjected to a competency-based assessment by using the six core competencies outlined by the American Board of Medical Specialties and the Accreditation Council for Graduate Medical Education as a framework. Furthermore, keywords were extracted for the CME program names based on the International Classification of Primary Care. Visual analysis was performed via VOSviewer software, facilitating a content-based evaluation of the programs. Results A total of 6,607 items were obtained. A total of 3,815 CME programs were subjected to statistical analysis, and 2,895 CME programs were comprehensively evaluated for content and capability. A diverse range of CME providers were identified, with hospitals and publishing/education companies being the primary providers. Since 2019, a significant increase in online CME offerings has been noted. However, the regional distribution of the CME programs was uneven, with Shanghai, Zhejiang, and Beijing leading but western China lagging. Furthermore, most programs focused on patient care and medical knowledge in competency-based CME evaluations, with less emphasis on interpersonal and communication skills. Content-based CME evaluations revealed that the teaching focus is the diagnosis, treatment, and primary care management of elderly patients and chronic diseases such as diabetes and hypertension. Conclusions Our findings underscore the essential role of CME in equipping GPs with the competencies required to navigate the evolving landscape of medical knowledge and practice, suggesting a more systematic, relevant, and individualized approach to training GPs. Therefore, there is an opportunity to increase the quality of primary care and contribute to the Healthy China 2030 Plan.